Assessing Critical Thinking Skills in STEM-PjBL Learning: An Exploration on Wave Topics for High Schools Student - Nurul Farhana Haris; Sulaeman, Nurul Fitriyah; Subagiyo, Lambang; Syam, Muliati (Universitas Jember, 2025)
In the 21st century, students need to master the 4C skills (Critical thinking, Creativity, Communication and Collaboration). One of the skills that is the focus of this research is critical thinking. This study aims to determine the critical thinking skills of high school students after learning with the Science – Technology – Engineering – Mathematics (STEM)- Project Based Learning (PjBL) model. The type of research used is quasi experiment with a posttest only control design research. The sampling technique in this study is cluster random sampling with a sample of 30 students of SMA Negeri 11 Samarinda. The assessment instruments used are in the form of validated Student Worksheets and critical thinking test instruments that have been adapted from previous research. The results of this study show that using the STEM-PjBL model on wave topics can significantly enhance students' critical thinking skills, as seen from the average Student Worksheet score of 83.3%, which falls into the very high category. Additionally, based on the test instrument results, students' abilities are categorized as high, with a score percentage of 81.1%. The STEM-PjBL learning model can be used to train students' critical thinking skills. The critical thinking ability was measured using instruments consisting of Student Worksheets rubrics and tests in the form of post-tests.Keywords: STEM-PjBL, Critical Thinking, Wave